2022
DOI: 10.3390/ijms23169255
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Sphingolipid Rheostat in Gliomas

Abstract: Gliomas are highly aggressive cancer types that are in urgent need of novel drugs and targeted therapies. Treatment protocols have not improved in over a decade, and glioma patient survival remains among the worst of all cancer types. As a result, cancer metabolism research has served as an innovative approach to identifying novel glioma targets and improving our understanding of brain tumors. Recent research has uncovered a unique metabolic vulnerability in the sphingolipid pathways of gliomas that possess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 196 publications
(352 reference statements)
0
12
0
Order By: Relevance
“…In IDH1 mut gliomas, the S1P-to-ceramide rheostat is tilted towards high ceramide levels (Fig. 1A, 12,13 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In IDH1 mut gliomas, the S1P-to-ceramide rheostat is tilted towards high ceramide levels (Fig. 1A, 12,13 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we demonstrated that in IDH1 mut glioma, D-2HG, the product of IDH1 mutant enzyme produces an increase in monounsaturated fatty acid (MUFA) levels 11 . These increased MUFA are incorporated into ceramides, tilting the S1P-to-ceramide rheostat toward apoptosis 12,13 . Therefore, for the first time, it has been described the rheostat imbalance in IDH mut gliomas, to be the opposite of that known in IDH wt gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…Our demonstration that the knock-down of SMPD3 , the critical gene involved in ceramide production, increases the proliferative status of IDH-O cells in vitro and in vivo is in keeping with the sphingolipid rheostat switching in a pro-proliferative (i.e., S1P-producing) direction. Given the importance of this lipid conversion in regulating the growth of multiple tumor types, it is not surprising that drugs targeting the sphingolipid rheostat have now reached clinical trials for glioma patients 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in experimental models such as the rat C6 glioma cell line, expression of Smpd3 inhibits tumour growth 16 . These data suggest that the sphingolipid rheostat is shifted in opposite directions in IDH-mutant versus IDH-wildtype gliomas – with the balance towards pro-proliferative in GBM and anti-proliferative/pro-apoptotic in IDH-O and IDH-A 10-12 .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation